Renoprotective Effect of Centaurea choulettiana Pomel (Asteraceae) Leaves on Cisplatin-induced Oxidative Stress and Renal dysfunction in Mice - Bioud Kenza, Azzouzi Djihane, Benrebai Mouad, Mekkiou Ratiba, Benayache Samir, Benayache Fadila, Ameddah Souad (Journal of Applied Pharmaceutical Science, 2017)
Several species of Centaurea genus are continuously used in traditional medicine. Cisplatin (CP) is still regarded as one of the principal chemotherapeutic agents used in the therapy of many human malignancies. However, the clinical use of CP is limited due to its serious nephrotoxicity. In this study we have investigated the possible renoprotective effects of n-BuOH extract of Centaurea choulettiana Pomel leaves (BECC) in a cisplatin-induced nephropathy model. The single dose administration of cisplatin (8 mg/kg body weight; ip) resulted in acute renal deterioration as evidenced by the elevation of blood urea nitrogen (BUN) level, creatinine level, renal oxidative stress associated with extensive vacuolization of epithelial cell, swelling, desquamation and necrosis as histopathological alterations. The mice pretreatment with BECC (150 mg/kg; 10 days) attenuated the increase renal dysfunction markers, creatinine (80.15 %), BUN (57.58%) and suppressed malondialdehyde (MDA) (54.90 %). The BECC pretreatment restored GSH level (63.29%) and reversed the antioxidant enzymes, CAT (67.61%), SOD (68.16%), GPX (66.38 %) and the GST activities (70.18 %). The vitamin E pretreatment suppressed MDA level (74.10%) preserved GSH level (80.59 %) and CAT, SOD, GPX, GST activities (84.35%, 85.68 %, 77.90 %, 86.63 %) respectively. These finding indicated the comparable preventive effect of both BECC and vitamin E. The histopathological protection was clearly confirmed by the reduction of renal MPO Level (52.21%). Both biochemical results and histopathological evidence showed the renoprotective potential of Centaurea choulettiana, which was able to ameliorate CP-induced and renal dysfunction through its antioxidant capacity.
Keywords: Cisplatin, Centaurea choulettiana Pomel, Nephrotoxicity, Oxidative Stress.